Sex Differences in Cue Competition Effects With a Conditioned Taste Aversion Preparation - Angulo, Rocio; Bustamante, Javier; Estades, Vania; Ramírez, Valeska; Jorquera, Belén (Frontiers in Behavioral Neuroscience, 2020)
This study aimed to test whether male and female rats might show differences in cue competition effects in a conditioned taste aversion (CTA) model. Experiment 1 tested for sex differences in overshadowing. After conditioning of a flavored compound AB or only one simple flavor A (being A and B a solution of sugar 10% and salt 1%, counterbalanced), consumption of the A solution at test was larger in the former than in the latter case only in males. Thus, the usual effect of overshadowing was observed in males but not in females. Experiment 2 examined sex differences in blocking with the same stimuli used in Experiment 1. After conditioning of AB, the consumption of B was larger for the animals that previously received a single conditioning trial with A than for those that received unpaired presentations of A and the illness. As observed in Experiment 1, the typical blocking effect appeared only in males but not in females. The present findings thus support the hypothesis that sex dimorphism might be expressed in classical conditioning, or at least, in cue competition effects such as overshadowing and blocking with a taste aversion model.